Предмет: Алгебра, автор: motomoto2077

решите уравнение(3x-1)^2-9(x+1) (x-1)=0

Ответы

Автор ответа: alexokmail
0

(3x-1)² - 9(x+1)(x-1) = 0

9x² - 6x + 1 - 9x² + 9 = 0

-6x + 10 = 0

x = 10/6 = 5/3 = 1⅔

Автор ответа: Aspirant2022
1

Ответ:

x=\frac{5}{3} или x=1\frac{2}{3}

Объяснение:

(3x-1)^2-9(x-1)(x+1)=0\\(9x^2-6x+1)-9(x^2-x+x-1)=0\\9x^2-6x+1-9(x^2-1)=0\\9x^2-6x+1-9x^2+9=0\\-6x+10=0\\-6x=-10\\x=\frac{-10}{-6}\\x=\frac{10}{6}\\x=\frac{5}{3}\\x=1\frac{2}{3}

Похожие вопросы
Предмет: Химия, автор: Дэнчик3636